Exacerbation of Liver Tumor Metastasis in twist1a+/xmrk+ Double Transgenic Zebrafish following Lipopolysaccharide or Dextran Sulphate Sodium Exposure - Jeng-Wei Lu; Yuxi Sun; Liang-In Lin; Dong Liu; Zhiyuan Gong (MDPI AG, 2021)
The poor prognosis for patients with hepatocellular carcinoma (HCC) is related directly to metastasis. The Twist1 gene encodes for a transcription factor essential to embryogenesis. It has also been shown to promote epithelial-to-mesenchymal transition (EMT), invasion, and metastasis; however, there is currently no in vivo evidence that Twist1 plays a role in the metastasis of liver tumors. Zebrafish are increasingly being used as an alternative cancer model. In the current study, an adult-stage zebrafish HCC model was used to examine the synergistic effects of twist1a and xmrk, a well characterized oncogene, during HCC metastasis. We also examined the effects of two inflammatory agents, lipopolysaccharides (LPS) and dextran sulfate sodium (DSS), on the hepatocyte-specific expression of transgenic twist1a and xmrk. The conditional overexpression of twist1a and xmrk was shown to promote liver tumor metastasis in zebrafish, resulting in increased apoptosis and cell proliferation as well as tumor maintenance and propagation independent of the inherent EMT-inducing activity of xmrk. Exposing twist1a+/xmrk+ transgenic zebrafish to LPS or DSS was shown to promote metastasis, indicating that the overexpression of twist1a and xmrk led to crosstalk between the signaling pathways involved in EMT. This study provides important evidence pertaining to the largely overlooked effects of signaling crosstalk between twist1a and xmrk in regulating HCC metastasis. Our results also suggest that the co-expression of twist1a/xmrk in conjunction with exposure to LPS or DSS enhances HCC metastasis, and provides a valuable in vivo platform by which to investigate tumor initiation and metastasis in the study of liver cancer.